A study on the application of adaptive reuse in selected old houses turned into restaurants in Quezon City - Villegas, Wyneth Lane D. (College of Home Economics, University of the Philippines Diliman, 2019)
Using a multiple case study approach, this research sought to determine how selected old houses repurposed into restaurants addressed the interior spatial considerations required in a food and beverage facility in terms of safety and sanitation. This study investigated the history of the selected old houses and analyzed for their compliance with the HACCP guidelines and Chapter III of the Code on Sanitation of the Philippines. Fire safety and employee comfort and safety guidelines were also included in the safety assessment. Three restaurants in Quezon City were purposively selected as case subjects for this thesis. Data gathering includes site observation, personal semi-structured interview, and photo documentation. Results of this study indicate that the interiors of two out of three of the selected old houses repurposed into restaurants were fully rehabilitated to address the interior spatial considerations required for food and beverage facilities in terms of safety and sanitation. Adaptive reuse was applied mainly to address the function of a food and beverage facility and not for the purpose of conserving the interior elements for their heritage value. The researcher recommends to further study old houses repurposed into restaurants, preferably registered ancestral houses. It is also recommended to interview the interior designers or architects who worked on the renovation of the selected old houses as they may give more design-centered insights.